Computing in Civil Engineering (2011) 2011
DOI: 10.1061/41182(416)60
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Effective Quality Assessment of As-Is Building Information Models and 3D Laser-Scanned Data

Abstract: Documenting as-is conditions of buildings using 3D laser scanning and Building Information Modeling (BIM) technology is being adopted as a practice for enhancing effective management of facilities. Many service providers generate as-is BIMs based on laser-scanned data. It is necessary to conduct timely and comprehensive assessments of the quality of the laser-scanned data and the as-is BIM generated from the data before using them for making decisions about facilities. This paper presents the data and as-is BI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 4 publications
0
23
0
Order By: Relevance
“…analysis or scheduling functionalities, the required LoD of objects' attributes and relations has to be defined, such as durations, dependencies or precedence information. Some LoD in literature are depicted in Table 5, whose definitions differ in geometric accuracy, quality or completeness of semantic information [71,152]. …”
Section: Accuracy and Capabilitymentioning
confidence: 99%
“…analysis or scheduling functionalities, the required LoD of objects' attributes and relations has to be defined, such as durations, dependencies or precedence information. Some LoD in literature are depicted in Table 5, whose definitions differ in geometric accuracy, quality or completeness of semantic information [71,152]. …”
Section: Accuracy and Capabilitymentioning
confidence: 99%
“…Recent work has shown that object-based recognition techniques based on Scan-vs-BIM frameworks indeed enable the recognition of 3D BIM objects in TLS data for supporting progress and dimensional quality control (Bosché, 2008;Bosché, 2009;Kim, 2013;Tang, 2011;Turkan, 2011;Turkan, 2013). Similar approaches are also investigated using 3D point clouds generated through photogrammetry instead of TLS (Golparvar-Fard, 2009;Golparvar-Fard, 2013).…”
Section: Scan-to-bim and Scan-vs-bimmentioning
confidence: 99%
“…Three dimensional (3D) Terrestrial Laser Scanning (TLS), also called LADAR (Laser Detection and Ranging), has been considered by many as the best available technology to capture 3D information on a project with accuracy and speed, with a wide range of applications in the AEC/FM industry (Stone, 2001;Tang, 2011;Jacob, 2008). Laser scanning has been proven to be valuable for construction managers to help them for many tasks such as progress monitoring, quality control and facility/infrastructure management (Biddiscombe, 2005;Bosché, 2008;Lee, 2012;Lijing, 2008;Park, 2007;Qui, 2008;Valero, 2013;Xiong, 2013;Yen, 2008).…”
Section: Progress Tracking In the Aec Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…These 3D imaging sensors capture existing structural and terrestrial conditions accurately, objectively, and with greater continuity than any manual metrology methods. Despite these benefits, the potential of 3D imaging for applications like automated progress tracking [1] and automated dimensional compliance control [2][3][4][5][6][7][8][9] remains limited because isolating the object of interest from the collected data remains a manual process. Manually extracting information from the raw 3D images and running analysis is painstaking, requires many man-hours and specialized personnel training, and therefore discourages adoption by industry.…”
Section: Introductionmentioning
confidence: 99%